Pay the bribe or take the high road: dilemma of a young female Tanzanian entrepreneur. Issue 1 (25th February 2020) - Galperin, Bella L.; Enueme, Chinenye Florence; Dixon, Deirdre Painter
Abstract : Theoretical basis: The purpose of this paper is to raise the question of whether having ethical values dictate actions at defining moments and builds upon theoretical frameworks in ethics, entrepreneurship and national culture. Three ethical approaches recommended for this case are: ends-based, virtue-based and rules-based. Research methodology: The methods of data collection were both primary and secondary. Primary data were collected through face to face and phone interviews with the primary subject. Secondary data were obtained through research journals and articles. Case overview/synopsis: This case study illustrates the experiences of a young female entrepreneur in Tanzania, Africa. It investigates the role of cultural practices, unemployment, corruption and ethics in shaping business decisions. The Tanzanian culture and business climate typically view women in traditional roles, while men dominate in corporate roles. These factors limit the ability of women to succeed. Elisa King is determined to pursue her dream to create a business beneficial to her community. To realize her dream, King finds herself in an ethical dilemma brought on by an overall corrupt culture. Complexity academic level: This case is appropriate for undergraduate- and graduate-level courses with an ethics component.